2013
DOI: 10.1159/000356505
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hypoxia in the Intervertebral Disc on the Biological Behaviors of Rat Adipose- and Nucleus Pulposus-Derived Mesenchymal Stem Cells

Abstract: Adipose-derived mesenchymal stem cells (ADMSCs) and nucleus pulposus-derived mesenchymal stem cells (NPMSCs) are two cell candidates for cell-based therapies for intervertebral disc (IVD) regeneration. However, little work has been done to determine the influence of hypoxia in the IVD on the biological behaviors of ADMSCs and NPMSCs. This study aimed to investigate the viability, proliferation and differentiation of rat ADMSCs and NPMSCs in the hypoxic environment of IVD in vitro. ADMSCs and NPMSCs isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
52
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 38 publications
2
52
1
Order By: Relevance
“…Certain studies have reported that these stem cells lack viability, proliferation and matrix biosynthesis under conditions resembling the IVD microenvironment, which negatively influences the biological and metabolic vitality of stem cells and impairs their repair potential (16,17). In recent years, increasing evidence supported the existence of nucleus pulposus MSCs (NPMSCs) in the nucleus pulposus (18)(19)(20)(21)(22)(23)(24). They possess a similar capacity of chondrogenic differentiation to that of BMSCs (18) and have better adaptability to the harsh IVD microenvironment than ADMSCs (24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain studies have reported that these stem cells lack viability, proliferation and matrix biosynthesis under conditions resembling the IVD microenvironment, which negatively influences the biological and metabolic vitality of stem cells and impairs their repair potential (16,17). In recent years, increasing evidence supported the existence of nucleus pulposus MSCs (NPMSCs) in the nucleus pulposus (18)(19)(20)(21)(22)(23)(24). They possess a similar capacity of chondrogenic differentiation to that of BMSCs (18) and have better adaptability to the harsh IVD microenvironment than ADMSCs (24).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that NPMSCs may be a good candidate cell for IVD regeneration by cell therapy. Previous studies have proved that NPMSCs can be isolated from normal and degenerative nucleus pulposus (18)(19)(20)(21)(22)(23)(24). However, the biological properties of stem cells are crucial for the regenerative effects of cell therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies [Li et al, 2013;Han et al, 2014] and many others [Blanco et al, 2010;Wu et al, 2017;Molinos et al, 2018] have demonstrated that the IVD itself contains MSCs. Blanco et al [2010] identified human NP-derived (NP)-MSCs from human degenerative discs, and found that these cells fulfilled nearly all the morphological, immunophenotypical, and differentiation criteria described by the International Society of Cell Therapy for MSCs.…”
mentioning
confidence: 97%
“…The condition in degenerated disc is characterized by low oxygen tension, limited nutrition, acidic pH, and high osmolarity, which may negatively influence the function or even survival of any implanted cells. 4,6,[12][13][14] To overcome harsh condition in disc, previous literatures proposed pre-conditioning cells before implantation 6 and appropriately differentiated cells could survive and synthesize matrix in situ. 10 With this in mind, we designed this study to investigate the potential effect of chondrogenic pre-differentiation on the regeneration of adipose-derived mesenchymal stem cells (ADSCs) in a harsh IVD-like condition.…”
mentioning
confidence: 99%